Phytoplankton community as bioindicators in aquaculture media Tilapia (Oreochromis niloticus) exposed to detergent and pesticide waste - Yusrizal Akmal; Rindhira Humairani; Muliari Muliari; Hanum Hanum; Ilham Zulfahmi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2021)
Phytoplankton is a bio-indicator of fertility in waters. This study aims to determine the impact of detergent and pesticide waste on the phytoplankton community structure in in tilapia aquaculture media. The phytoplankton identification stage was carried out at the MIPA Laboratory Almuslim University. The parameters studied were phytoplankton abundance, diversity index, uniformity index, dominance index, and water quality parameters. The results of this study showed that detergent and pesticide waste at the end of the study had caused a decrease in the abundance value of phytoplankton by 3,250 individual/L and 3,750 individual/L. In the control treatment, the highest phytoplankton composition was dominated by Chaetoceros sp., while the pesticide and detergent treatments were dominated by Golenkenia sp. and Microcystis sp. Exposure to detergent and pesticide waste reduced the diversity index value, the phytoplankton uniformity index value. At the beginning of the study, it has a moderate diversity index (H '= 2.485–3.072), while at the end of the study it shows low diversity (H' = 2.111–2.375). Furthermore, at the beginning and at the end of the study there was a decrease in the uniformity index value (E = 0.87–1.01) and (H '= 0.88–0.94).